Efficacy of different Potassium Sources on Quantitative and Qualitative Character of Litchi cv. Bombai grown in Indo-Gangetic Plain of West Bengal - Das, Kaushik; Dutta, Pallab (International Journal of Bio-resource and Stress Management, 2022)
A field experiment was carried out at Regional Research Station, New Alluvial Zone, Bidhan Chandra Krishi Viswavidyalaya, Gayeshpur, Nadia, West Bengal, India during September 2014 to July 2017 to study the effect of different sources of potassium on fruit growth, yield and quality of Litchi cv. Bombai grown in Indo-gangetic plain of West Bengal. The experiment was laid out in Randomized Block Design consisting of seven treatments with three replications. All the plants were uniform in growth, 12 years of age and healthy spaced at 10×10 m2. The results revealed that the application of different sources of potassium significantly improved the physico-chemical qualities and leaf mineral content of litchi. Among the different sources of potassium in the study, application of KNO3 @ 2% along with fixed doses of N @ 1000 g and P2O5 @ 500 g-1 plant-1 year-1 showed maximum vegetative growth in terms of plant height (5.00 m), spread (N-S and E-W) while application of K2SO4 @ 2% along with fixed doses of N @ 1000 g and P2O5 @ 500 g plant-1 year-1 showed highest fruit retention m-2 (32.50 no), yield (72.60 kg plant-1), fruit weight (23.03 g), fruit length (4.08 cm), breadth (3.30 cm), aril weight (15.99 g), TSS (19.17 °Brix), total sugar (14.98 %), lowest reducing sugar (11.19%) with highest Vitamin C (32.83 mg 100 g-1), Anthocyanin content (38.02 mg 100 g-1)and highest mineral content (N, P, K, Ca, B and Zn) of the leaf.